Promoting wellness among surgical patients through a structured perioperative care in DMC - Pedres, Jelane Camilan
This study sought to compare the effect of the current and suggested set-up of perioperative nursing on patient's anxiety, understand of surgical experience, awareness of self-care activities. It also sought to find out nurses' acceptability and job satisfaction and also surgeons' preference of the set-ups.